2019
DOI: 10.1002/anie.201901459
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Amphiphilic Conjugated Polymers for Inhibiting Amyloid β Assembly

Abstract: Protein misfolding and aberrant aggregations are associated with multiple prevalent and intractable diseases. Inhibition of amyloid assembly is apromising strategy for the treatment of amyloidosis.R eported here is the design and synthesis of areactive conjugated polymer,apoly(p-phenylene vinylene) derivative,f unctionalizedw ith p-nitrophenyl esters (PPV-NP) and it inhibits the assembly of amyloid proteins, degrades preformed fibrils,a nd reduces the cytotoxicity of amyloid aggregations in living cells.PPV-NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 43 publications
0
69
0
1
Order By: Relevance
“…S9 and S10, † a click reaction was promoted in a Cu-treated AD model of CL2006 worms aer 12 h. Organotypic brain slice cultures largely preserve brain architecture and possess major disease features, providing a practical platform for direct medication and real-time monitoring therapeutic effects. 38,39 Therefore, this technology is widely used for studying neurodegenerative diseases. In addition, it has been observed that copper levels are elevated in senile plaques, the hippocampus, and cortex of AD model mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9 and S10, † a click reaction was promoted in a Cu-treated AD model of CL2006 worms aer 12 h. Organotypic brain slice cultures largely preserve brain architecture and possess major disease features, providing a practical platform for direct medication and real-time monitoring therapeutic effects. 38,39 Therefore, this technology is widely used for studying neurodegenerative diseases. In addition, it has been observed that copper levels are elevated in senile plaques, the hippocampus, and cortex of AD model mice.…”
Section: Resultsmentioning
confidence: 99%
“…S26 †). 39 We next investigated whether Ab40-Cu aggregates could act as a catalyst for the in situ synthesis of the bifunctional drug 6 in cells. It has been proven that silica nanoparticles can penetrate the blood-brain barrier (BBB) by inducing tight junction loss and cytoskeleton arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…1 Nanotechnology has been widely used in the field of tumor theranostics. 2 The nanoparticle sizes play an essential role in the enrichment of nanoparticles at the tumor sites. 3 Compared with large-sized nanoparticles, small-sized nanoparticles show advantages of deep tissue penetration and long circulation lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…The synaptic dysfunction impairs the synaptic plasticity and hippocampal LTP formation causing neuronal damage, memory loss and cognitive decline under AD pathogenesis (4). Contemporary studies have shown that Aβ aggregation species interact with the plasma membrane and promote the internalization of misfolded Aβ peptides by punch holes through the membrane (5,28,29). These results motivated us to evaluate the anti-AD properties of TGR63 in an APP/PS1 double transgenic AD mouse model.…”
Section: Inhibition Of Aβ Aggregation and Associated Toxicity: Microsmentioning
confidence: 99%